2012
DOI: 10.1186/1742-2094-9-198
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2B receptor-mediated leukemia inhibitory factor release from astrocytes protects cortical neurons against excitotoxicity

Abstract: BackgroundNeuroprotective and neurotrophic properties of leukemia inhibitory factor (LIF) have been widely reported. In the central nervous system (CNS), astrocytes are the major source for LIF, expression of which is enhanced following disturbances leading to neuronal damage. How astrocytic LIF expression is regulated, however, has remained an unanswered question. Since neuronal stress is associated with production of extracellular adenosine, we investigated whether LIF expression in astrocytes was mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 88 publications
0
31
0
Order By: Relevance
“…Such mechanism would be essential to avoid an hypoenergetic crisis, which might lead to cell death. Indeed, A 2B R activation has been linked with increased survival of hippocampal and cortical cells under oxygen-glucose deprivation [30][31][32]. Hence, A 2B Rs seem to generally assist the homeostasis of brain cells in a manner similar to that occurring in the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanism would be essential to avoid an hypoenergetic crisis, which might lead to cell death. Indeed, A 2B R activation has been linked with increased survival of hippocampal and cortical cells under oxygen-glucose deprivation [30][31][32]. Hence, A 2B Rs seem to generally assist the homeostasis of brain cells in a manner similar to that occurring in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Although normally metabolic boosters (nootropics) do not mitigate the outcome of neurodegenerative disorders, A 2B R agonists eventually possess multiple beneficial actions including boosting cerebral glucose metabolism and increasing cell survival apart from effects on energy metabolism [30][31][32]. Therefore, further studies are invited to evaluate the clinical potential of A 2B R agonists in both animals and man.…”
Section: Discussionmentioning
confidence: 99%
“…HFS and activation of A2BRs can trigger the release of cytokines from astrocytes [84,85], and this has been proposed as a metaplastic mechanism for inhibiting LTP both homo-and heterosynaptically [86], and indeed, we have recently shown that A2BR activation can generate a cell-wide inhibition of LTP [40]. It is therefore possible that priming stimulation in stratum oriens modulates plasticity in stratum radiatum by eliciting widespread cytokine release from astrocytes, a hypothesis we consider worthy of future investigation.…”
Section: Intercellular Pathwaysmentioning
confidence: 99%
“…LIF is a neurotrophic cytokine, which, in the brain, is mainly produced by astrocytes. Elevated levels of LIF were shown to promote the maturation of oligodendrocytes [208], and LIF was found to protect primary neurons against excitotoxicity [209]. Moreover, in the EAE mouse model LIF was demonstrated to protect axons in the brain from acute inflammatory damage [210].…”
Section: Tnfr2-possible Downstream Targets In Neurodegenerationmentioning
confidence: 99%